PURA SEBAGAI BENTUK PENERAPAN KONSEP KETUHANAN SAGUNA BRAHMA - Komang Heriyanti (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2019)
Hindu faith in supporting the improvement of Sradha and Bhakti has a holy place called temple. The meaning of the temple in general is a place of worship to God in various aspects for Hindus ranging from the smallest family level to the largest region. In general the function of the place of worship is as a mean to worship God with all its manifestations and to worship ancestral holy spirit at all levels. In the holy book and the book of Vedanta, God is mentioned with two different views, namely God who is tangible (Saguna Brahma) as the form of the gods and God who are not tangible. In the view of Saguna Brahma there are many symbols of religius symbols such as the life of the Hindu peoples in Bali that are inseparable from the holy place and various upakara. Temple is one of the applications of the Saguna Brahma concept. Keywords: Temple, Saguna Brahma, Hindu